К изучению жужелиц трибы Pogonini (Coleoptera, Carabidae) фауны Украины - Петрусенко, С.В.; Петрусенко, А.А. (Вестник зоологии, 1970)
В УССР найдено 17 видов жужелиц трибы Pogonini. Они представлены
следующими зоогеографическими элементами: среднеазиатскими (восемь видов), средиземноморскими (четыре вида), восточносредиземноморскими (три вида), древнесредиземноморским (один вид) и западнопалеоарктическим (один вид). Прослежены их суточная и сезонная динамика, трофические связи, перечислены враги. Указаны новые местонахождения для девяти видов, из которых Pogonus virens впервые найден на Украине. In the Ukraine 17 species of Carabidae, tribe Pogonini are found. They are presented by the Middle Asian (8 species), Mediterranean (4 species), East-Mediterranean (3 species), ancient-Mediterranean (1 species) and wet-palearctic (1 species) zoogeographic elements. Spreading of these beetles in the Ukrainian SSR and their distribution according to biotopes, diurnal and seasonal dynamics and trophical relations were observed. The enemies are enumerated (7 species of birds). New habitats of 9 species of beetles are mentioned. Pogonus virens is found in the Ukraine for the first time.